Innovation management in a small enterprise in the state of Amazonas - Coelho, Moisés Israel Belchior de Andrade (Revista Gestão da Produção Operações e Sistemas, 2014)
This work aimed to identify and propose practical business focused on innovation management for small enterprises using the Temaguide model. The literature review focused on aspects related to innovation management and the management model used in the study. The work took place in a small enterprise in the food sector of the city of Manaus. The study took the form of an action research.The research approach is characterized as qualitative and indirect documentation (documentary research and literature), intensive direct observation (observation and interview), and extensive direct observation (forms) were the research techniques used. Results are presented in the application of the steps in the Temaguide enterprise model and innovations implemented. The relevance of this work consists of the presentation and adoption of a model for innovation management, in a small enterprise, which can be applied by the company itself or in collaboration with a university. Keywords: Innovation management. Entrepreneurship. Small Enterprise. Amazonas.